Novel Analytic Methods Needed for Real-Time Continuous Core Body Temperature Data. (January 2017) - Hertzberg, Vicki; Mac, Valerie; Elon, Lisa; Mutic, Nathan; Mutic, Abby; Peterman, Katherine; Tovar-Aguilar, J. Antonio; Economos, Eugenia; Flocks, Joan; McCauley, Linda
Affordable measurement of core body temperature (Tc ) in a continuous, real-time fashion is now possible. With this advance comes a new data analysis paradigm for occupational epidemiology. We characterize issues arising after obtaining Tc data over 188 workdays for 83 participating farmworkers, a population vulnerable to effects of rising temperatures due to climate change. We describe a novel approach to these data using smoothing and functional data analysis. This approach highlights different data aspects compared with describing Tc at a single time point or summaries of the time course into an indicator function (e.g., did Tc ever exceed 38 °C, the threshold limit value for occupational heat exposure). Participants working in ferneries had significantly higher Tc at some point during the workday compared with those working in nurseries, despite a shorter workday for fernery participants. Our results typify the challenges and opportunities in analyzing Big Data streams from real-time physiologic monitoring.